18‐2: Invited Paper: LCD Enhancement Films Enabling High‐Performance Near‐IR Transparent LCDs. Issue 1 (28th June 2021) - Acharya, Bharat R.; Sousa, Matthew; Fabick, Ryan; Taylor, Robert; Rosen, David; Cole, Matthew; Sanford, Quinn; Long, Shine; Liu, Desmond; Liu, Yang; Chen, Jennifer; Wang, Richens; et al.
Abstract : The conventional light management films used to enhance display performance of a conventional edge‐lit LCD reflect, scatter, and refract both visible and near infrared light and therefore do not allow imaging though LCDs. We have developed an entirely new class of display enhancement films and coatings that enable imaging through LCDs in near IR wavelengths while maintaining high display quality. Using this Near IR Transmission System (NITS) we demonstrate under display fingerprint sensing for LCD‐based smart phones.